Compassionate use of contezolid in a toddler with severe community-acquired pneumonia induced by staphylococcus aureus: a case report and follow-up - Liu, Hui-Ying; Bi, Xiao-Fei; Wang, Ya-Jun; Xie, Feng-Jie; Zhang, Hong; Zhu, Yu-Cheng; Zhang, Yan; Wang, Zhi-Hui; Wu, Di; Meng, Huan; Lin, Yi-Lu; Liu, Lin-Qiong; et al. (Frontiers in Pediatrics, 2024)
Background Initial choices of antimicrobial therapy for most cases of community-acquired pneumonia (CAP) in children under 5 years of age are typically based on local epidemiology, risk factors assessment, and subsequent clinical parameters and positive cultures, which can lead to the underdiagnosis and underestimation of lung infections caused by uncommon pathogens. Contezolid, an orally administered oxazolidinone antibiotic, gained approval from the National Medical Products Administration (NMPA) of China in June 2021 for managing complicated skin and soft tissue infections (cSSTI) caused by staphylococcus aureus (SA), streptococcus pyogenes, or streptococcus agalactis. Owing to its enhanced safety profile and ongoing clinical progress, the scope of contezolid's clinical application continues to expand, benefiting a growing number of patients with Gram-positive bacterial infections. Case summary In this report, we present the first use of contezolid in a toddler with severe CAP caused by SA, aiming to avoid potential adverse drug reactions (ADRs) associated with vancomycin and linezolid. Conclusion Although contezolid has not been officially indicated for CAP, it has been shown to be effective and safe in the management of SA-induced severe CAP in this toddler, suggesting its potential as an alternative option in the dilemma, especially for patients who are susceptible or intolerant to ADRs associated with first-line anti-methicillin-resistant staphylococcus aureus (MRSA) antimicrobial agents.